A parametric study of the techno‐economics of direct CO2 air capture systems using solid adsorbents. Issue 7 (23rd April 2019) - Sinha, Anshuman; Realff, Matthew J.
Abstract: Direct air capture (DAC) can help in reduction of atmospheric CO2 levels by capturing CO2 from disperse emission sources. We analyze DAC process through solid adsorbent and perform comprehensive energy and techno‐economic analysis for different parametric scenarios. The parameters are varied such that it reflects list of possible cases of DAC solid adsorbent systems ranging from worst case to best case situations. A mid‐range estimate has also been analyzed which considers the parameter values feasible with the current state of the art. The modeling results for the mid‐range estimate indicate that the cost of DAC lies between $86 and 221 per tCO2, the thermal energy range varies from 3.4 to 4.8 GJ per tCO2 captured and the electrical energy range varies from 0.55 to 1.12 GJ per tCO2 captured. For the best and worst case scenarios, the cost of DAC ranges from $14 to 1, 065 per tCO2, thermal energy ranges from 1.85 to 19.30 per tCO2 captured and the electrical energy ranges from 0.08 to 3.79 GJ per tCO2 captured. Flux and intensity estimates have been performed which shows higher flux and lower intensity of DAC process as compared to a tropical tree.